Biomass-derived 3D solar evaporator with enhanced sterilization performance for seawater desalination and wastewater treatment - Siqi Wang; Shuang Wang; Hongjun Chen; Pengjie Xian; Huang Zhou (Desalination, 2026)

Bisphenol a exposure induces low back pain associated with intervertebral disc degeneration via BIRC3-mediated nucleus pulposus cell senescence - Tao Kang; Hongjun Huang; Dun Liu; Junfei Feng; Yongqi Huang; Song Wang; Hongyuan Xu; Yuwang Du; Zuyuan Huang; Rongqing He; Hua Jiang (Toxicology and Applied Pharmacology, 2026)

Soil organic carbon and pH govern the divergent trajectories of organic and inorganic sulfur under long-term fertilization - Haotian Shi; Miao Lei; Shaomin Huang; Hongjun Gao; Lu Zhang; Dongchu Li; Shulan Zhang; Xianlu Yue; Qingxu Ma; Wenju Zhang (Journal of Cleaner Production, 2026)

Dual regulatory role of Penicillium oxalicum and Lolium perenne in bauxite residue soilization: Labile organic carbon dynamics and community assembly - Yufei Zhang; Yifan Jiang; Qishuang Li; Hongjun Dong; Feng Zhu; Xianchao Zhang; Graeme J. Millar; Shiwei Huang; Shengguo Xue (Journal of Environmental Sciences, 2026)

Targeting delivery of shikonin via cryo-shocked tumor cells for non-small cell lung cancer treatment - Huanhuan Huang; Hui Ren; Feiye Liu; Wenyue Lv; Mengzhen Xu; Huiheng Feng; Haoli Liu; Dong Chen; Peng Zhao; Hongjun Li; Jing Qin (Chemical Engineering Journal, 2026)

System-Level Optimization of AUV Swarm Control and Perception: An Energy-Aware Federated Meta-Transfer Learning Framework with Digital Twin Validation - Zinan Nie; Hongjun Tian; Yijie Yin; Yuhan Zhou; Wei Li; Yang Xiong; Yichen Wang; Zitong Zhang; Yang Yang; Dongxiao Xie; Manlin Wang; Shijie Huang (Journal of Marine Science and Engineering, 2026)
Deep-sea exploration increasingly relies on Autonomous Underwater Vehicles (AUVs) to enable persistent, wide-area surveying in harsh and uncertain environments. In practice, however, deployments are constrained by tight energy budgets and bandwidth-limited, intermittent acoustic links, which complicate mission-level coordination. Moreover, many existing systems treat perception and control as loosely coupled modules, often resulting in redundant sensing, inefficient communication, and degraded overall performance—particularly under heterogeneous sensing modalities and shifting geological conditions. To address these challenges, we propose a hierarchical Federated Meta-Transfer Learning (FMTL) framework that tightly integrates collaborative perception with adaptive control for swarm optimization. The framework operates at three levels: (1) Representation Learning aligns heterogeneous sensors in a shared latent space via a physics-informed contrastive objective, substantially reducing communication overhead; (2) Meta-Learning Adaptation enables rapid transfer and convergence in new environments with minimal data exchange; and (3) Energy-Aware Control realizes closed-loop exploration by coupling Federated Explainable AI (FXAI) with decentralized multi-agent reinforcement learning (MARL) for path planning under energy constraints. Validated in high-fidelity hardware-in-the-loop simulations and a digital-twin environment, FMTL outperforms state-of-the-art baselines, achieving an AUC of 0.94 for target identification. Furthermore, an energy–intelligence Pareto analysis demonstrates a 4.5× improvement in information gain per Joule. Overall, this work provides a physically consistent and communication-efficient blueprint for the optimization and control of next-generation intelligent marine swarms.

Organic electron donor limitation triggers metabolic trade-offs in anaerobic granular sludge: The pivotal role of Fe-mediated electron bifurcation - Bochuang Huang; Yangyang Li; Jinhao Zhu; Juncong Zou; Dexin Wang; Chunping Yang; Hongjun Han; Wencheng Ma (Chemical Engineering Journal, 2026)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Antibacterial properties of folic acid-based hydrogel loaded with CeCDs and its potential application in food preservation - Mengzhen Wang; Li Zeng; Hongjun Chen; Senhao Hu; Chengzhi Huang; Shujun Zhen; Lei Zhan (Food Chemistry, 2025)

Unveiling environmental adaptability of magnetite-mediated Feammox system: Multiple pathways identification, metabolic responses and engineering potential analysis - Xiangzhuang Fu; Yangyang Li; Weiwei Huang; Dexin Wang; Chunping Yang; Hongjun Han (Chemical Engineering Journal, 2025)

Glycerol-driven optimization of algae-bacteria symbiosis systems for enhanced lipid production and self-flocculation - Yuwei Zhang; Jiaheng Teng; Jiahui Huang; Liguo Shen; Hongjun Lin; Renjie Li; Xiang Cai; Zeqiong Xu; Meijia Zhang (Journal of Environmental Chemical Engineering, 2025)

Effect of ultrasound-assisted phosphates treatment on solubilization and stable dispersion of rabbit Myofibrillar proteins at low ionic strength - Chang Su; Yuxin Huang; Jiaxin Chen; Hongjun Li; Dong Zhang; Yong Tang (Food Chemistry, 2025)

Molecular characterization of large yellow croaker (Larimichthys crocea) coagulation factor Ⅶ-like and its function on macrophage proliferation and polarization - Yueming Chen; Han Zhao; Shuangshuang Cao; Hongjun Xie; Jieyu Huang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Polyimide-multiwalled carbon nanotubes composite as electrochemical sensing platform for the simultaneous detection of nitrophenol isomers - Jianzheng Wang; Chunying Liu; Ziao Di; Jiayu Huang; Hongjun Wei; Minjie Guo; Xiaoliang Yu; Nan Li; Jin Zhao; Bowen Cheng (Chemosphere, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

A negative-carbon planning method for agricultural rural industrial park integrated energy system considering biomass energy and modern agricultural facilities - Dewei Jiang; Hongjun Gao; Shuaijia He; Yuan Huang; Junyong Liu (Journal of Cleaner Production, 2024)

Effects of biochar produced from distiller grains on agronomic performances of sorghum (Sorghum bicolor L.) and greenhouse gas emissions from soil - Hongjun YANG; Suyi ZHANG; Jingyu HU; Jianguo HUANG; Zonghua AO; Xiaoqin WANG; Zhe LI; Xuepin LIAO (Pedosphere, 2024)

Visualizing of engineered five-helix bundle protein for blocking SARS-CoV-2 variants in live animals - Jianzhong Xian; Zhijun Li; Hongbin Huang; Lei Bi; Zhifeng Guan; Guolong Huang; Min Yang; Zhizeng Gao; Jijin Yao; Zhongzhen Su; Hongjun Jin (Chemical Engineering Journal, 2024)

Quasi-FeCo-MOF/CoS amorphous Nanosheets: A stable and highly active catalyst for electrocatalytic water splitting and monosaccharide oxidation - Yanqiu Xu; Qiang Zhang; Nana Wang; Lijun Huang; Xiao Zhang; Hongjun Lin; Yanchao Xu; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2024)

Characteristics, Distribution Patterns, and Classification of Volcanic Reservoirs in the Huanghua Depression, Bohai Bay Basin, China - Jian Huang; Changqian Ma; Shihui Zhang; Muyue Xu; Da Lou; Chongbiao Leng; Mutian Qin; Hongjun Li (Journal of Earth Science, 2024)

Rice-fish coculture without phosphorus addition improves paddy soil nitrogen availability by shaping ammonia-oxidizing archaea and bacteria in subtropical regions of South China - Xing Liu; Daolin Sun; Huaqiao Huang; Jiaen Zhang; Hongjun Zheng; Qi Jia; Min Zhao (Science of The Total Environment, 2024)

Spatial heterogeneity plays a vital role in shaping the structure and function of estuarine carbon-fixing bacterial communities - Jianrong Xu; Hongxia Ming; Kaijia Ren; Dongwei Li; Huiling Huang; Jiajie Li; Kuishuang Shao; Hongjun Li; Jingfeng Fan (Marine Environmental Research, 2024)

Chronic exposure to gestodene impairs reproductive system in adult female zebrafish (Dania rerio) - Hong Zou; HongJun Yu; YunYi Huang; YanFang Guo; MeiXin Ye; LiPing Hou (Chemosphere, 2024)

Mg2+ addition: Unlocking optimized treatment performance and anti-fouling property in microalgal-bacterial membrane bioreactors - Fei Huang; Yu Zhao; Shilei Chen; Hongjun Lin; Jiaheng Teng; Xiang Cai; Meijia Zhang (Science of The Total Environment, 2024)

Emerging disinfection byproducts 3-bromine carbazole induces cardiac developmental toxicity via aryl hydrocarbon receptor activation in zebrafish larvae - Yingying Liu; Xudong Jin; Yanan Ye; Zeqiong Xu; Zhongkun Du; Huachang Hong; Haiying Yu; Hongjun Lin; Xianfeng Huang; Hongjie Sun (Environmental Pollution, 2024)

Residues of Polycyclic Aromatic Hydrocarbons in Breast Milk Collected from Jinhua (China) and the Influence of Exercise Habit: Levels and the Potential Health Effects - Qianfeng He; Xiaoge Zhang; Lihong Kuang; Haotian Xu; Yizhong Hou; Fangqu Huang; Zeqiong Xu; Hongjie Sun; Wenjing Deng; Hongjun Lin; Huachang Hong (Exposure and Health, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

Effective strategies for reclamation of saline-alkali soil and response mechanisms of the soil-plant system - Xin Xu; Lin Guo; Shaobo Wang; Xuanyi Wang; Meng Ren; Pengjie Zhao; Ziyi Huang; Hongjun Jia; Jinhang Wang; Aijun Lin (Science of The Total Environment, 2023)

Comprehensive evaluation of the risk system for heavy metals in the rehabilitated saline-alkali land - Xin Xu; Lin Guo; Shaobo Wang; Meng Ren; Pengjie Zhao; Ziyi Huang; Hongjun Jia; Jinhang Wang; Aijun Lin (Journal of Environmental Management, 2023)

Optimizing aeration intensity to enhance self-flocculation in algal-bacterial symbiosis systems - Jiahui Huang; Sihan Cheng; Yuwei Zhang; Jiaheng Teng; Meijia Zhang; Hongjun Lin (Chemosphere, 2023)

Genetic sequencing provides insights into molecular and genetic mechanisms of Lysobacter enzymogenes HYP18 involved in soil organic nitrogen and phosphorus mobilization and plant growth promotion - Liyuan Peng; Jianguo Huang; Chunyang Huang; Hongjun Yang (Plant and Soil, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Effect of the random distribution of gravel particles on the mechanical behaviors of conglomerate - Jun Wei; Hualin Liao; Bin Huang; Ning Li; Hongjun Liang; Bo Zhou; Quan Zhang; Long Chen; Hui Feng (Arabian Journal of Geosciences, 2023)

Bibliometric analysis and mini-review of global research on pyroptosis in the field of cancer - Wenwen Wang; Wenhuizi Sun; Han Xu; Yao Liu; Chenlu Wei; Siqiao Wang; Shuyuan Xian; Penghui Yan; Jiajun Zhang; Hongjun Guo; Hengwei Qin; Jie Lian; et al. (Apoptosis, 2023)

Multi-walled carbon nanotube induced liver injuries possibly by promoting endoplasmic reticulum stress in Cyprinus carpio - Xiaochan Gao; Chaoran Ma; Hongjun Wang; Chunnuan Zhang; Yong Huang (Chemosphere, 2023)

Stable oxic-anoxic transitional interface is beneficial to retard soil carbon loss in drained peatland - Liangfeng Liu; Jianqing Tian; Hongjun Wang; Dan Xue; Xinya Huang; Ning Wu; Meng Wang; Xingliang Xu; Changhui Peng; Yanfen Wang; Huai Chen (Soil Biology and Biochemistry, 2023)

Novel mesocellular silica foam supported poly(amidoxime-ethyleneimine) network for fast and highly efficient uranium extraction from seawater - Jiajia Yang; Yun Li; Tian Tian; Haitao Shi; Zia Ahmad; Ningbo Geng; Jing Jin; Yanqiang Huang; Haijun Zhang; Hongjun Fan; Jiping Chen (Chemical Engineering Journal, 2023)

Mechanism analysis and experimental verification of the bulging vibration characteristic of a fluid-solid metamaterial - Zichun Yi; Zhiwei Zhang; Jiankun Huang; Hongjun Xiang; Caisong He; Lanhua Liu (Engineering Structures, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

Multi-omics analysis reveals copper-induced growth inhibition mechanisms of earthworm (Eisenia fetida) - Yanliang Zhang; Jinqi Zhao; Na Sa; Chenyu Huang; Wenyu Yu; Tianxiao Ma; Hongjun Yang; Fang Ma; Siqi Sun; Chaochun Tang; Weiguo Sang (Environmental Pollution, 2023)

Engineering metal–organic frameworks (MOFs) based thin-film nanocomposite (TFN) membranes for molecular separation - Die Ling Zhao; Fan Feng; Liguo Shen; Zhengyi Huang; Qipeng Zhao; Hongjun Lin; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Mitigation of protein fouling by magnesium ions and the related mechanisms in ultrafiltration process - Hui Zou; Jiahui Huang; Meijia Zhang; Hongjun Lin; Jiaheng Teng; Zhengyi Huang (Chemosphere, 2023)

Life Cycle Greenhouse Gas Emission Assessment for Using Alternative Marine Fuels: A Very Large Crude Carrier (VLCC) Case Study - Jinjin Huang; Hongjun Fan; Xiangyang Xu; Zheyu Liu (Journal of Marine Science and Engineering, 2022)
The International Maritime Organization (IMO) has set decarbonisation goals for the shipping industry. As a result, shipowners and operators are preparing to use low- or zero-carbon alternative fuels. The greenhouse gas (GHG) emission performances are fundamental for choosing suitable marine fuels. However, the current regulations adopt tank-to-wake (TTW) emission assessment methods that could misrepresent the total climate impacts of fuels. To better understand the well-to-wake (WTW) GHG emission performances, this work applied the life cycle assessment (LCA) method to a very large crude carrier (VLCC) sailing between the Middle East and China to investigate the emissions. The life cycle GHG emission impacts of using alternative fuels, including liquified natural gas (LNG), methanol, and ammonia, were evaluated and compared with using marine gas oil (MGO). The bunkering site of the VLCC was in Zhoushan port, China. The MGO and LNG were imported from overseas, while methanol and ammonia were produced in China. Four production pathways for methanol and three production pathways for ammonia were examined. The results showed that, compared with MGO, using fossil energy-based methanol and ammonia has no positive effect in terms of annual WTW GHG emissions. The emission reduction effects of fuels ranking from highest to lowest were full solar and battery-based methanol, full solar and battery-based ammonia, and LNG. Because marine ammonia-fuelled engines have not been commercialised, laboratory data were used to evaluate the nitrous oxide (N2O) emissions. The GHG emission reduction potential of ammonia can be exploited more effectively if the N2O emitted from engines is captured and disposed of through after-treatment technologies. This paper discussed three scenarios of N2O emission abatement ratios of 30%, 50%, and 90%. The resulting emission reduction effects showed that using full solar and battery-based ammonia with 90% N2O abatement performs better than using full solar and battery-based methanol. The main innovation of this work is realising the LCA GHG emission assessment for a deep-sea ship.

The addition of sawdust reduced the emission of nitrous oxide in pig manure composting by altering the bacterial community structure and functions - Chao Liu; Jiao Yan; Qian Huang; Hongjun Liu; Cece Qiao; Rong Li; Biao Shen; Qirong Shen (Environmental Science and Pollution Research, 2022)

Combination of Polyethylene Glycol-Conjugated Urokinase Nanogels and Urokinase for Acute Ischemic Stroke Therapeutic Implications - Ding Nan; Haiqiang Jin; Di Yang; Weiwei Yu; Jingjing Jia; Zemou Yu; Hui Tan; Yongan Sun; Hongjun Hao; Xiaozhong Qu; Yining Huang (Translational Stroke Research, 2021)

Strength behavior of red clay reinforced by basalt chopped fiber - Ningyu Zhao; Hongjun Wu; Zhengyu Huang (Arabian Journal of Geosciences, 2021)

Alternative reverse genetics system for influenza viruses based on a synthesized swine 45S rRNA promoter - Kai Wang; Qi Huang; Zhiwei Yang; Kezong Qi; Hongmei Liu; Hongjun Chen (Virus Genes, 2017)

The SAR studies on FAP inhibitors as tumor-targeted agents - Jun Xu; Sichao Huang; Tiantian Zhang; Nong Wu; Hongjun Kang; Shaohui Cai; Weizai Shen (Medicinal Chemistry Research, 2015)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Relationships between the West Asian subtropical westerly jet and summer precipitation in northern Xinjiang - Yong Zhao; MinZhong Wang; AnNing Huang; HongJun Li; Wen Huo; Qing Yang (Theoretical and Applied Climatology, 2014)

The Alteration of MiR-222 and Its Target Genes in Nickel-Induced Tumor - Jing Zhang; Yang Zhou; Lin Ma; Shunquan Huang; Ruijin Wang; Rongrong Gao; Youjun Wu; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2013)

Spatio-temporal distribution of nitrogen in the undulating littoral zone of Lake Taihu, China - Hongjun Wang; Jinwei Lu; Weidong Wang; Peisheng Huang; Chengqing Yin (Hydrobiologia, 2007)

Chromosomally located gene fusions constructed in Acinetobacter sp. ADP1 for the detection of salicylate - Wei E. Huang; Hui Wang; Hongjun Zheng; Linfeng Huang; Andrew C. Singer; Ian Thompson; Andrew S. Whiteley (Environmental Microbiology, 2005)
Summary Acinetobacter sp. ADP1 is a common soil‐associated bacterium with high natural competency, allowing it to efficiently integrate foreign DNA fragments into its chromosome. This property was exploited to engineer salicylate‐inducible luxCDABE and green fluorescent protein (GFP) variants of Acinetobacter sp. ADP1. Specifically, Acinetobacter sp. ADPWH _lux displayed the higher sensitivity when comparing the two variants (minimum detection c . 0.5–1 µM salicylate) and a faster turnover of the lux marker gene, making it suitable for whole‐cell luminescence assays of salicylate concentration. In contrast, the longer maturation and turnover times of the GFP protein make the Acinetobacter sp. ADPWH _gfp variant more suited to applications involving whole‐cell imaging of the presence of salicylate. The sensitivity of the luxCDABE variant was demonstrated by assaying salicylate production in naphthalene‐degrading cultures. Assays using ADPWH _lux specifically mapped the kinetics of salicylate production from naphthalene and were similar to that observed by high‐performance liquid chromatography (HPLC) data. However, ADPWH _lux exhibited the higher sensitivity, when compared with HPLC, for detecting salicylate production during the first 24 h of naphthalene metabolism. These data demonstrate that the engineered Acinetobacter variants have significant potential for salicylate detection strategies in laboratory and field studies, especially in scenarios where genetic stability of the construct is required for in situ monitoring.